ORGANOMETRIC PARAMETERS OF THE RECTUM DURING THE PERINATAL PERIOD OF HUMAN ONTOGENESIS - Vitenok, O.Ya.; Rohovyi, Yu.Ye. (World of Medicine and Biology, 2012)
A morphometric study of the rectum on 53 autopsied specimens of 4-10 month old fetuses has been carried out. Two periods of an accelerated development (in months 5, 8-10) and two periods of relative slowing down (in months 6 and 7) of the rectum development have been revealed. During the period of a retarded development in 7 months old fetuses the length and width of the supraampullar portion of the rectum and the parieto-calcaneal length are associated between the mselves by a significant multiple regression relationship that reflects synergism of biosynthetical processes among these structures.